2021
DOI: 10.1073/pnas.2107963118
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of P[II] rotavirus evolution and host ranges under selection of histo-blood group antigens

Abstract: Group A rotaviruses cause severe gastroenteritis in infants and young children worldwide, with P[II] genogroup rotaviruses (RVs) responsible for >90% of global cases. RVs have diverse host ranges in different human and animal populations determined by host histo-blood group antigen (HBGA) receptor polymorphism, but details governing diversity, host ranges, and species barriers remain elusive. In this study, crystal structures of complexes of the major P[II] genogroup P[4] and P[8] genotype RV VP8* receptor–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Based on nucleotide sequence identities in VP7 and VP4 genes, RVA is further classified into G and P genotypes, respectively. The P[8], P[4], and P[6] genotypes in the P[II] genogroup are responsible for over 90% of human infections worldwide, and are considered to have originated from P [I] RVs with an animal host origin and evolved the ability to infect humans (Xu et al, 2021). Currently, RVs have been reported from a variety of bat species belonging to Rhinolophidae, Vespertilionidae, Hipposideridae, Pteropodidae, Emballonuridae, and Rhinopomatidae (Esona et al, 2010;He et al, 2013He et al, , 2017Mishra et al, 2019;Waruhiu et al, 2017;Xia et al, 2014).…”
Section: Potential Of Interspecies Transmissions Of Bat Rvs To Mammal...mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on nucleotide sequence identities in VP7 and VP4 genes, RVA is further classified into G and P genotypes, respectively. The P[8], P[4], and P[6] genotypes in the P[II] genogroup are responsible for over 90% of human infections worldwide, and are considered to have originated from P [I] RVs with an animal host origin and evolved the ability to infect humans (Xu et al, 2021). Currently, RVs have been reported from a variety of bat species belonging to Rhinolophidae, Vespertilionidae, Hipposideridae, Pteropodidae, Emballonuridae, and Rhinopomatidae (Esona et al, 2010;He et al, 2013He et al, , 2017Mishra et al, 2019;Waruhiu et al, 2017;Xia et al, 2014).…”
Section: Potential Of Interspecies Transmissions Of Bat Rvs To Mammal...mentioning
confidence: 99%
“…Li et al (2021) reported that the single amino acid mutation in the VP8* protein of bat P [3] genotype rotavirus obtained the ability to hemagglutinate the red blood cells, and this residue played an important role in the ligand recognition and may contribute to the cross-species transmission. However, other specific glycans, such as mucin and histo-blood group antigens (HBGAs), can interact with VP8* and affect RVs tropism in different hosts (Xu et al, 2021). Thus, the role of species-specific glycans in the cross-species transmission need to be further determined, which is of great significance for determining host range and epidemiology, species barrier mechanism, and cross-species transmission.…”
Section: Potential Of Interspecies Transmissions Of Bat Rvs To Mammal...mentioning
confidence: 99%
“…A more recent study provided structural evidence for the interactions of the P [8] genotype with the secretor HBGA precursor, but binding experiments did not support interactions with Lewis A or B HBGAs [7]. Further structural studies proposed the hypothesis that evolution of genogroup P[II] RV (P [8], P [4] and P [6]) progressed from animals to humans under the selection of type 1 HBGAs guided by stepwise host synthesis of type 1 ABH and Lewis HBGAs [66].These laboratory observations have been supported by epidemiological studies showing that P [8] and P [4] genotypes infect Lewis B secretor children preferentially and P [6] infects Lewis-negative children preferentially, irrespective of the secretor phenotype [6,[67][68][69][70]. The rotavirus P [6] genotype is more prevalent in sub-Saharan African and South-East Asian countries than in other populations, coinciding with a higher proportion of Lewis-negative phenotypes, reaching up to 30% of this population [60,68,71,72].…”
Section: Host Genetics and Health Outcomesmentioning
confidence: 99%
“…VP8* from P [8], P [4], P [6], P [14], P [11], and P [19] genotypes recognize the secretor HBGAs. Regarding P [8] and P [4] genotypes, there were controversial studies since some determined that they bind the Le b and H type-1 [25][26][27][28], while others report no Le b binding for these genotypes [29,30]. P [6] binds the H1 antigen but was reported not to bind Le b [31], whereas P [19] binds mucin core glycans with the GlcNAc-β-1→6-GalNAc motif and the type-1 HBGA precursor [32].…”
Section: Hbgas and Rvmentioning
confidence: 99%
“…P [6] binds the H1 antigen but was reported not to bind Le b [31], whereas P [19] binds mucin core glycans with the GlcNAc-β-1→6-GalNAc motif and the type-1 HBGA precursor [32]. Other studies also documented that P [9], P [14], and P [25] strains interact with the A antigen [24,33], whereas P [11] interacts with single and repeated Nacetyl-lactosamine, the type-2 precursor glycan [34]. The HBGAs interactions with VP8* have been investigated by X-ray crystallography in some cases, identifying sugar binding pockets which are different from the sialic acid binding site identified in animal RV [30].…”
Section: Hbgas and Rvmentioning
confidence: 99%